Income Shifting Incentives and Tax Haven Utilization: Evidence from Multinational U.S. Firms - Richardson, G.; Taylor, Grantley (Pergamon, 2015)
This paper examines the association between a series of income shifting incentives including multinationality, transfer pricing aggressiveness, thin capitalization, intangible assets and tax haven utilization. Our empirical analysis is based on a sample of 286 multinational U.S. firms over the 2006–2012 period (2002 firm-years). Our regression results show that multinationality, transfer pricing aggressiveness, thin capitalization and intangible assets are positively associated with tax haven utilization. Our results are consistent based on several robustness checks.